2022
DOI: 10.3390/ph15070823
|View full text |Cite
|
Sign up to set email alerts
|

GCase Enhancers: A Potential Therapeutic Option for Gaucher Disease and Other Neurological Disorders

Abstract: Pharmaceutical chaperones (PCs) are small compounds able to bind and stabilize misfolded proteins, allowing them to recover their native folding and thus their biological activity. In particular, lysosomal storage disorders (LSDs), a class of metabolic disorders due to genetic mutations that result in misfolded lysosomal enzymes, can strongly benefit from the use of PCs able to facilitate their translocation to the lysosomes. This results in a recovery of their catalytic activity. No PC for the GCase enzyme (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 102 publications
0
24
0
Order By: Relevance
“…The pharmacological chaperone is believed to induce or stabilize the proper conformation of the misfolded but catalytically active glucosidase, preventing its premature degradation by ER-associated degradation (ERAD). 65 66 Beyond Gaucher disease, PC may provide a new generation of therapeutic agents to treat Parkinson’s disease. Recent findings have indeed demonstrated that defects in GCase activity increase the risk of developing this severe neurodegenerative disorder.…”
Section: Multivalency Spin-offsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacological chaperone is believed to induce or stabilize the proper conformation of the misfolded but catalytically active glucosidase, preventing its premature degradation by ER-associated degradation (ERAD). 65 66 Beyond Gaucher disease, PC may provide a new generation of therapeutic agents to treat Parkinson’s disease. Recent findings have indeed demonstrated that defects in GCase activity increase the risk of developing this severe neurodegenerative disorder.…”
Section: Multivalency Spin-offsmentioning
confidence: 99%
“…Pharmacological chaperone therapy (PCT) is based on the use of inhibitors that are able to increase the residual hydrolytic activity of the mutant enzymes at sub-inhibitory concentrations. 65 PCT is a further illustration of the maxim penned by La Fontaine in The Lion and the Rat: "There's none so small but you his aid may need." Indeed, PCT is based on the fact that the defective enzyme, a massive biomolecule, is 'rescued' by its low molecular weight inhibitor.…”
Section: Multivalency Spin-offsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the PC‐enzyme complex reaches the lysosome, the large amount of stored substrate is supposed to displace the PC allowing the recovery of the enzyme activity [4d,5] . Only few examples of non‐competitive inhibitors, that interact with allosteric sites, have been reported as good PCs [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Iminosugars are glycomimetics with a basic nitrogen atom replacing the endocyclic oxygen in carbohydrates . As structural analogues of sugars, they offer the opportunity to mimic the biological action of carbohydrates while circumventing their drawbacks, thereby representing valuable and promising tools in medicinal chemistry, mainly due to their ability to inhibit glycosidases and glycosyltransferases. Most of the research has been focused on the synthesis of five- and six-membered iminosugars (polyhydroxylated pyrrolidines and piperidines, respectively) . Polyhydroxyazepanes, their seven-membered ring analogues, also named polyhydroxyperhydroazepines or seven-membered iminocyclitols, have been investigated much less frequently.…”
mentioning
confidence: 99%